From Pixels to Peace: Unraveling the Multifaceted Narrative of Religious Tolerance in Social Media - Hidayat, M. Riyan; el-Feyza, Muhafizah (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
Religious tolerance has contributed to a national campaign related to religious moderation through the Indonesian Ministry of Religious Affairs which continues to be promoted to a wide audience in Indonesia. All elements take part in the realisation of religious tolerance to fight radicalism, extremism, and ideas that refer to disintegration. Furthermore, the narrative of religious tolerance aims to build peace in diversity. In an increasingly sophisticated world, religious narrative campaigns do not only occur in the religious institution but also occur in the social media space, as happened on Instagram such as @toleransi.id. There are around 38 thousand followers on this account and their followers continue to grow so that the nuances of the narrative of religious tolerance become colourful and rich. This research utilises library research using qualitative methods and the lens of virtual ethnography theory. By posting content from the @toleransi.id account, the research results show that community interaction in the media space in discussing religious tolerance shows a strong correlation between the real and virtual worlds. Second, it shows the interaction of virtual communities with a wider scope than in real communities. Third, the discussion of the theme focused on adjusting the context of the media account of tolerance.